1989
DOI: 10.1080/00071668908417131
|View full text |Cite
|
Sign up to set email alerts
|

Zinc, copper and iron utilisation by chicks fed various concentrations of zinc

Abstract: 1. Zinc, iron and copper interactions were examined in chicks (New Hampshire X Single Comb White Leghorn) grown individually in stainless steel cages and fed on purified diets with three concentrations of zinc: control (37 mg Zn/kg), moderate (100 mg Zn/kg) and excess (2000 mg Zn/kg) in three studies. 2. Chicks given either moderate or excess zinc excreted more than twice as much 65Zn from a test diet as those fed on the control diet. Thus chicks given the moderate amount of zinc had concentrations of zinc in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…Hepatic Zn increased more than 10-fold in that study, when the dietary concentration was increased to about 2200 mg/kg (Stahl et al, 1989). In mallards, liver concentrations (wet weight) increased from 54 to 401 mg/kg Zn as the dietary concentration increased from control concentrations to 3000 mg/kg (Gasaway & Buss, 1972).…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…Hepatic Zn increased more than 10-fold in that study, when the dietary concentration was increased to about 2200 mg/kg (Stahl et al, 1989). In mallards, liver concentrations (wet weight) increased from 54 to 401 mg/kg Zn as the dietary concentration increased from control concentrations to 3000 mg/kg (Gasaway & Buss, 1972).…”
Section: Resultsmentioning
confidence: 86%
“…For example, the whole body concentrations of Zn in songbirds from a site severely contaminated with Zn from smelting were less than 20% greater than those of songbirds from a reference site, although the A1 soil horizon of that contaminated site had more than 10 times the Zn concentration of the reference site (Beyer et al, 1985). In experimental studies on chickens, hepatic Zn concentrations (wet weight) remained constant as the dietary concentration was increased from 37 to about 110 mg/kg (Stahl et al, 1989).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Broilers receiving excess inorganic zinc accumulate a higher proportion of zinc in their tissues, and seem to present reduced iron turnover, as well as lower iron and copper concentrations in the liver and pancreas, and lower iron in tibia (Stahl et al, 1989). Patton (1997) suggested that the use of mineral chelates should made after further observations of their actions on animal metabolism.…”
Section: Performance Of Poultry Fed Chelated Mineralsmentioning
confidence: 99%